Clinical Significance of Ultrasound-Based Hemodynamic Assessment of Extracranial Internal Carotid Artery and Posterior Cerebral Artery in Symptomatic and Angiographic Evolution of Moyamoya Disease: A Preliminary Study - Zheng, Shuai; Ge, Peicong; Shi, Zhiyong; Wang, Jingzhe; Li, Yi; Yu, Tengfei; Zhang, Jinghan; Zhang, Hongxia; Zhang, Dong; He, Wen (Frontiers in Neurology, 2021)
ABSTRACT Objective: To investigate the hemodynamic changes using ultrasound according to digital subtraction angiography (DSA) findings and explore the association between ultrasound parameters and clinical symptoms of moyamoya disease (MMD). Methods: Hemodynamic parameters of extracranial internal carotid artery (EICA) and posterior cerebral artery (PCA) were evaluated by ultrasound. According to DSA findings, EICA parameters among Suzuki stages (stage Ⅰ-Ⅱ, Ⅲ-Ⅳ, and Ⅴ-Ⅵ), and PCA parameters among leptomeningeal system scores (score 0-2, 3-4, and 5-6) were compared, respectively. ROC analysis was performed based on the ultrasound parameters to distinguish stroke from non-stroke patients. Results: Forty patients with MMD were included in our study (16 men; median age, 37 years). The diameter (D), peak systolic velocity (PSV), end diastolic velocity (EDV) and flow volume (FV) of EICA decreased as the Suzuki stage advanced (D: P＜0.001; PSV: P＜0.001; EDV: P＜0.001; FV: P＜0.001). The PSV and EDV of PCA increased as the leptomeningeal system scores advanced (PSV: P＜0.001; EDV: P＜0.001). ROC analysis showed that the area under the curves (AUCs) based on the D and FV of EICA, the PSV and EDV of PCA and their combination were 0.688, 0.670, 0.727, 0.684 and 0.772, respectively, to distinguish stroke from non-stroke patients. Conclusions: Ultrasound parameters were related to DSA findings, ultrasound may be useful in predicting the clinical symptoms of patients with MMD. Future prospective studies with large sample sizes and long-term follow-up are needed to confirm our preliminary findings.